The effect of surgery on the levels of matrix metalloproteinases in patients with inguinal hernia - Strohalmová, Sabina; Levová, Kateřina; Kuběna, Aleš; Krška, Zdeněk; Hoskovec, David; Zima, Tomáš; Kalousová, Marta (Physiological research, 2021)
Matrix metalloproteinases (MMPs) are associated with the alteration of extracellular matrix. The purpose of this study was to investigate how the levels of matrix metalloproteinases and their inhibitors - TIMPs are influenced by the presence of inguinal hernia as well as by its surgical treatment. The studied group consisted of 25 patients with inguinal hernia and 21 healthy controls for comparison. Two blood samples - before and after the treatment were collected from patients. Serum concentrations of MMPs and TIMPs were analysed by multiplex immunoassays. There was a difference in circulating levels of MMPs in patients before the surgery compared to healthy controls - the concentrations of MMP-2 and MMP-9 were significantly lower (p=0.026, p=0.018, respectively). After the surgery, the levels of MMPs, especially MMP-2 (p<0.0001), were significantly decreased in patients compared to the preoperative values, apart from MMP-9. On the contrary, MMP-9 showed significant increase after the surgery (p<0.0001). Circulation levels of TIMP-2 in patients were significantly decreased in comparison with controls (p=0.004), whereas levels of TIMP-1 were similar to controls. Both tested metalloproteinase inhibitors showed a significant decrease in detected levels (TIMP-1 p=0.0004; TIMP-2 p<0.0001) after the procedure compared to the preoperative values. The levels of MMPs, especially MMP-2 and MMP-9, and their inhibitors TIMP-1 and TIMP-2 are involved by the presence of inguinal hernia as well as are influenced by the surgery.
Keywords: Hernia, Inguinal; Humans; lidé; Tissue Inhibitor of Metalloproteinase-1; Herniorrhaphy; inguinální hernie; Matrix Metalloproteinase 2; lidé středního věku; operace kýly; Treatment Outcome; tkáňový inhibitor metaloproteinasy 2; Middle Aged; Case-Control Studies; Female; matrixová metaloproteinasa 9; Male; Adult; Tissue Inhibitor of Metalloproteinase-2; Biomarkers; výsledek terapie; mužské pohlaví; tkáňový inhibitor metaloproteinasy 1; Aged; studie případů a kontrol; ženské pohlaví; matrixová metaloproteinasa 2; dospělí; biologické markery; Matrix Metalloproteinase 9; senioři